CREATING STUDENTS STUDY GROUP USING COOPERATIVE LEARNING METHOD TO IMPROVE THE STUDENTS VOCABULARY LEARNING - A. Putri Meylani Sugandi M; Hasnawati Latief; Ratu Yulianti Natsir (FKIP Unismuh Makassar, 2022)
Learning is the process of acquiring knowledge and mastering skills. However, there are obstacles in learning English, namely vocabulary mastery. Therefore, several interesting teaching methods were made so that students are interested in learning English. One of them is a cooperative method that will be used by researchers. The purpose of this study is that researchers want to see whether the use of cooperative learning methods can improve students' vocabulary knowledge, especially nouns.The research methodology used in this study was Classroom Action Research (CAR) which was carried out in two cycles with the aim of increasing students' vocabulary knowledge through the use of group cooperative learning methods. substantially improve students' vocabulary mastery at SMP Yapend Bungaya Makassar in the 2022 school year. Student learning achievement in cycle II is(75,3) much greater than in cycle I (65,3) and Diagnostic Tests (55,62). The cooperative learning method is able to substantially improve the vocabulary understanding of the second grade students of SMP Yapend Bungaya Makassar. Student achievement in the second cycle is greater than the first cycle as indicated by the Diagnostic Test..